The complete guide to growing your own fruits and berries : everything you need to know explained simply - Gault, Karen Szklany (Back to basics growing., 2011)
Leads you through the process of starting your own garden of fresh fruits and berries. You'll learn step-by-step methods for planting, harvesting and caring for your berry bushes, shrubs, and fruit trees.